Analysis of Barrier and Driver Factors to Risk Monitoring and Control Implementation in Construction Projects - Almutahir Almutahir; I Putu Artama Wiguna (Publikasi Indonesia, 2024)
Construction projects inherently involve risks. If proper risk management practices are not employed, the likelihood of cost overruns can reach more than 80%. Risk monitoring and control are essential processes in risk management; however, their implementation is inadequate in construction projects. This research analyzed the main barriers and drivers for implementing risk monitoring and control in construction projects. A questionnaire survey was conducted using a Likert scale to measure respondents' perceptions. Data were collected from 71 respondents: top management, project managers, project risk managers, and risk officers. This study employs descriptive analysis and factor analysis to achieve the objectives. The results indicate that the 19 identified barriers to risk monitoring and control were categorized into 4 main factors: lack of practice, lack of risk awareness, lack of incentives and having difficulty finding methods, and misperceptions about risk monitoring and control. Meanwhile, the 21 drivers were categorized into 5 main factors: management support, tools and information technology, organizational structure and communication, external environment, assigning responsibility, and contingency reserve.